Time-encoded golden angle radial arterial spin labeling: simultaneous acquisition of angiography and perfusion data - van der Plas, MCE; Schmid, S; Versluis, MJ; Okell, TW; van Osch, MJP (Wiley, 2021)
The goal of the current study was to combine a time-encoded pseudo-continuous arterial spin labeling (te-pCASL) scheme with a golden angle radial readout for simultaneous acquisition of angiography and perfusion images from one single dataset both in a very flexible single-slice approach as well as within a multi-slice setting. A te-pCASL labeling preparation and the golden angle radial readout were both used as a temporal resolution tool to retrospectively choose the temporal window for the reconstruction of both angiography and perfusion images from a single-slice dataset. The temporal window could be chosen retrospectively and adjusted to the hemodynamics of the volunteer on the scanner for the single-slice dataset. Angiographic images were reconstructed at a minimum temporal resolution of 69 ms. For the perfusion phase only the densely sampled center of k-space was included in the reconstruction. For a multi-slice acquisition, the golden angle radial readout allowed reconstruction of images with different spatial resolutions to provide angiographic and perfusion information over 10 slices. The te-pCASL preparation was used as the only source for dynamic information. The multi-slice acquisition shows the ability of the golden angle radial readout to display the inflow of the labeled blood into the arteries as well as the perfusion in the tissue with full brain coverage. By combining a te-pCASL preparation with a golden angle radial readout, single-slice high temporal resolution angiography and good quality perfusion images were reconstructed in a flexible manner from a single dataset. Optimizing the golden angle radial readout for reconstructions at multiple spatial resolutions, allows for multi-slice acquisition.